Implementation of the global laboratory leadership programme in Burkina Faso: lessons learned and processes toward sustainability - Emilie Dama; Abdoulaye Nikiema; Andre Coulibaly; Raoul Karfo; Issaka Yameogo; Fabienne Soudre; Alice Kiba; Charles Sawadogo; Isidore Bonkoungou; Habibata Zerbo; Lila Rahalison; Amanda Balish; et al. (Frontiers in Public Health)
IntroductionThe Global Laboratory Leadership Programme (GLLP) aims to foster and mentor current and emerging laboratory leaders to build, strengthen, and support national laboratory systems using a One Health approach. Six organizations, including the US Centers for Disease Control and Prevention, developed GLLP to address gaps in leadership and management skills, particularly in low- and middle-income countries. This work highlights lessons from implementing GLLP in Burkina Faso, including the approach to sustainability.MethodsA participatory implementation model was adopted, engaging key international and national stakeholders across all One Health sectors. From 2021 to 2023, Burkina Faso implemented the full GLLP learning package, which encompasses all nine competencies, projects, and mentoring. Following the completion of the pilot cohort’s training, a sustainability plan was developed, leading to the creation of a University Diploma in Laboratory Leadership and Management (UD-LLM) in 2024, with the training of its first cohort completed in 2025. For both the pilot and the UD-LLM cohorts, a monitoring and evaluation framework was applied throughout the process.ResultsA total of 44 participants from Burkina Faso and Mauritania were trained in both the pilot (18) and the first cohort of the UD-LLM (26). Participants from Burkina Faso (43) were from all One Health sectors and worked in laboratories across 10 institutions (public, private, and military) located in nine of the country’s 13 regions. A total of 117 projects including 10 capstone projects, were completed to address gaps identified at institutional or national levels with support from mentors. A low representation of candidates from the animal and environmental sectors was noted. Overall satisfaction with the training was reported for both cohorts.ConclusionBurkina Faso is the first country in the French-speaking African region with a sustained GLLP full package integrated into a university curriculum. The early engagement of country stakeholders across sectors ensured the country’s ownership and a path to sustainability. Maintaining a monitoring and evaluation framework is essential for continued improvement. This work demonstrates how early multisectoral engagement and academic integration of the GLLP can create a sustainable model for laboratory leadership development in resource-limited settings.